Numerical modeling of explosives and propellants - Mader, Charles L. (CRC Press, 1998)
Presents an introduction to the physics and chemistry of explosives and propellants. This book covers numerical modeling of detonation and reactive fluid dynamics. It offers scientists and engineers a picture of the state of explosive and propellant technology and numerical modeling.